Withania somnifera (Ashwagandha) a plant of many possibilities - Izabela Czyżewska; Piotr Michał Jarosz; Patrycja Wiśniewska (Kazimierz Wielki University, 2020)
Ashwagandha (Withania somnifera) has been long used in the traditional Ayurvedic system of medicine to enhance various kinds of disease processes and specially as a nervine tonic. Nowadays, its beneficial activities are still being searched.